H-Alpha Spectra of Early and Late Types Stars - N, Ahmad; M.Z, Zainuddin (Malaysian Journal of Science, 2003)
Preliminary results of basic analysis to study the properties of $H_α$ line of early and late type stars using spectroscopy technique are presented. Spectra of 12 stars brighter than $M_v$= 2.99 have been obtained at dispersion of 1.07Ãƒâ€¦/pixel using SBIG spectrograph at the prime focus of 12-inch telescope. The analyses of line profiles which considered on their full width at half maximum (FWHM), equivalent width (EW), central intensity or line depth ($R_c$) and central line were conducted under Visual Spectroscopy software. We have measured the profiles of $H_α$ line in B, A, F, K, and M types of stars. We found out that the profiles are strongest at A type and becomes weak as the stars evolved to the late types. It also shows that the line profile for the very early type star such as B is quite weak. The measurement of line profiles included the luminosity, which gave an estimation of their size.